2020
DOI: 10.1002/joc.6704
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of SM2RAIN precipitation datasets in comparison to gauge observations and hydrological modelling over arid regions

Abstract: Numerous satellite-based precipitation datasets have been successively made available. Their precipitation estimates rely on clouds properties derived from microwave and thermal sensors in a so-named 'top-down' approach. Recently, a 'bottom-up' approach to infer precipitation from soil moisture (SM) estimates has resulted in the release of two new precipitation datasets (P-datasets). One uses satellite-based SM estimates from the European Spatial Agency (ESA) Climate Change Initiative (CCI) (SM2RAIN-CCI) while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 85 publications
1
11
0
Order By: Relevance
“…Under the influence of multiple factors, the inversion data of SM2RAIN precipitation is relatively high in summer. [34]. Besides, through time comparison and analysis of runoff simulation results, it can be seen that SM2RAIN still has a certain application potential in the Qaraqash River basin.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Under the influence of multiple factors, the inversion data of SM2RAIN precipitation is relatively high in summer. [34]. Besides, through time comparison and analysis of runoff simulation results, it can be seen that SM2RAIN still has a certain application potential in the Qaraqash River basin.…”
Section: Discussionmentioning
confidence: 91%
“…SM2RAIN is a product that estimates precipitation based on soil moisture. At present, studies have shown that SM2RAIN can well capture the precipitation characteristics under drought conditions [33,34]. Brocca et al also pointed out that the performance of SM2RAIN in some areas lacking precipitation data is better than IMERG and GPCC [36].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, similar β and Vr values were observed for both wet and dry months. This seasonal variation is linked to the monthly precipitation total distribution [45]. Across Nigeria, the monthly precipitation totals are well (poorly) distributed between the maximum and minimum values during the dry season (wet season) (Figure 1).…”
Section: Spp Reliability On the National Scalementioning
confidence: 97%
“…However, such action prevents a robust comparison, as SPP sensitivity to the regional meteorological, topographic, and land cover characteristics induce substantial space and time reliability variation [26,43,44]. A recent study comparing seven satellite-based precipitation datasets over two distinct areas with similar precipitation patterns (i.e., South American Andean Plateau and Pakistan) shows that the most reliable SPP from one region to another is different [45].…”
Section: Precipitation Monitoring Across Remote Regionsmentioning
confidence: 99%
“…At the catchment outlet, the best models produced values of KGE of $0.65 and PBIAS of $6% for the MSWEP forcing dataset, KGE of $0.68 and PBIAS of $7%, for the IMERG dataset, and KGE of $0.66 and PBIAS of À1.7% for ERAforced models. Given the complex hydrological conditions of the basin and the large-scale gridded datasets used to force the hydrological model(Bain et al, 2023;Barkhordari et al, 2023;Beck et al, 2020;Satgé et al, 2021), these evaluation results suggest that calibrated DRYP models are skilful at simulating streamflow at the catchment outlet of the Ewaso Ng'iro basin.The calibrated DRYP models well capture the temporal variation of streamflow at the basin outlet (Archer's post, Figure1a) for all three forcing datasets (Figure2d), for example, during the large flow events in March 2003, December 2007 and December 2012, although they fail to well capture other flow events (e.g., December 2004, March 2010). Overall, there are high correlations between modelled and measured streamflow for all rainfall forcing datasets (Q MSWEP : r = 0.70, p < 0.001; Q ERA : r = 0.78, p < 0.001, and Q IMERG : r = 0.74, p < 0.001).…”
mentioning
confidence: 98%